2022
DOI: 10.1155/2022/5054507
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation of the Clinical Application Value of HR‐HPV DNA Combined with Liquid Based Cytology in Colposcopy of Cervical Cancer

Abstract: In order to investigate the clinical application value of HR-HPV DNA combined with liquid-based cytology in colposcopy of cervical cancer, a retrospective analysis is performed on 428 patients who underwent a cervical pathological examination in our hospital from May 2020 to December 2021. The pathological biopsy results are used as the gold standard to determine whether cervical lesions occurred in patients, and patients with positive gold standard results are included in the study group. The positive rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There were also 10 cases of menopause and 387 cases of non-menopausal. Pathological diagnosis was divided into CIN I (mild dysplasia; n=153 cases), CIN II (moderate dysplasia; n=101 cases), CIN III (severe dysplasia and carcinoma in situ ; n=86 cases) and cervical cancer (n=57) ( 20 ). The present study was reviewed and approved by the ethics committee of Jinan Licheng District Maternal and Child Health Care Family Planning Service Center, Jinan, Shandong, China.…”
Section: Methodsmentioning
confidence: 99%
“…There were also 10 cases of menopause and 387 cases of non-menopausal. Pathological diagnosis was divided into CIN I (mild dysplasia; n=153 cases), CIN II (moderate dysplasia; n=101 cases), CIN III (severe dysplasia and carcinoma in situ ; n=86 cases) and cervical cancer (n=57) ( 20 ). The present study was reviewed and approved by the ethics committee of Jinan Licheng District Maternal and Child Health Care Family Planning Service Center, Jinan, Shandong, China.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%